Mali excels itself - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Rice production in Mali continues to show a steady growth. The region s largest rice producer attained 724,000 t in the 1999/2000 season; 743,000 t in the 2000/2001 season and 840,000 t in the last one. Climatic conditions have been favourable but...